(untitled) (International Journal of Agriculture and Sustainable Development, 2021)
Economic output, jobs, household sustenance, and industrial expansion are all influenced by a country’s water infrastructure and policy. Water is essential to all aspects of human existence, it is a highly contentious issue. Water policies will be examined in this study utilizing quantitative textual data analysis. To swiftly review massive amounts of data, researchers can use the text mining of these water rules to uncover interconnections and surface important connections between entities. Although interregional and inter-state water disputes are identified as a problem, the issue is not addressed in depth in the language of India’s water plan. As a result of the importance of the Indus River, Pakistan’s strategy in these areas is more cross-cutting and multi-disciplinary. According to the United Nations Sustainable Development Goals (SDGs), Pakistan has to improve its water policy in water-sensitive urban designs, natural-hazard risk management, and mapping of water sector growth. Both governments can benefit from each other’s water policies due to these quantitative discoveries.